Online Monitoring Method for Opening and Closing Time of 10 kV Spring Energy Storage Circuit Breaker Based on Transient Electrical Signal Characteristic Point Marking and Self-Calibration - Weng, Liting; Xiao, Jiangtao; Zhang, Zhaochuang; Wang, Jingang; Wen, Yuchuan; Zhang, Fan; Zhang, Xingyu; Ma, Lingyi; Zhao, Pengcheng (Energies (Basel), 2024)
Among all circuit breaker faults, mechanical failures account for a considerable proportion, and online monitoring of their mechanical characteristics is of great practical significance. The opening and closing time is a very important feature of the mechanical characteristics of the circuit breaker. Online monitoring of the opening and closing time of the circuit breaker has always been the focus and difficulty of the intelligent technology of switchgear. In this paper, for a 10 kV spring energy storage vacuum circuit breaker, transient voltage and current signals are innovatively used to calibrate the opening time, breaking time, and closing time, and an online monitoring method for the opening and closing time of a vacuum circuit breaker based on transient electrical signals is proposed. An online monitoring platform was built and a multi-group closing test was carried out to simulate the power plant environment. The opening and closing time samples of a spring energy storage vacuum circuit breaker were measured and compared with the measurement results of the mechanical properties tester. The comparison results show that this method has good stability, and the calculation error is controlled within 1% after self-calibration, which provides a new idea for the online monitoring research of the mechanical characteristics of spring energy storage vacuum circuit breakers.